The Influence of Personality and Professionality on Personnel Work Performance at the Police Headquarters' Registration Bureau - Riswanda Linge; Enjang Sudarman; Sukiman Sukiman (Dinasti International Journal of Digital Business Management, 2026)
This study aims to determine and analyze in depth the influence of personality on employee work performance, the influence of professionalism on employee work performance, and the influence of personality and professionalism simultaneously on Personnel Work Performance at a WASSIDIK BUREAU OF THE POLICE HEADQUARTERS. This study uses a quantitative approach, namely an approach that emphasizes the collection and processing of data in the form of numbers so that the results of the analysis can be interpreted objectively and measurably. However, this study is also supplemented by qualitative data as support, such as verbal statements in questionnaires, open comments, and the results of consultations or short interviews between researchers and informants to enrich understanding of the variables studied. The study population amounted to 927 employees, while the sample used was 90 respondents selected based on sampling techniques appropriate to the research needs. Hypothesis testing was carried out using the SPSS version 29 analysis tool, which is able to test the relationship between variables simultaneously and accurately. The results of the study indicate that personality (X1) and work motivation/professionalism (X2) have a positive and significant influence on employee achievement or performance (Y) partially. Furthermore, the R-Square test result of 0.412 indicates that 41.2% of the variation in employee performance can be explained by these two variables, while the remaining 58.8% is influenced by factors outside this study, such as the work environment, leadership, workload, and other organizational factors. These findings emphasize the importance of personality and professional development in improving employee performance